Ecoenzyme Menuju Agroindustri yang Berkelanjutan Desa Sumber Waru Kecamatan Binakal Bondowoso Jawa Timur - Priyono, Teguh Hadi; Santoso, Edy; Yunitasari, Duwi; Jumiati, Aisah; Istiyani, Nanik (Universitas Nusantara PGRI Kediri, 2025)
Unmanaged organic waste will be a problem in itself. The solution offered to overcome the problem of wasting food waste in the form of vegetables and fruits is to make eco enzymes. Making integrated eco enzymes is by utilizing all waste in the vegetable/agricultural farming system, in the integrated agricultural cultivation process into a zero waste bioenergy cycle. If every household and farmer uses their waste to produce environmentally friendly enzymes, it can stop kitchen waste from polluting our land/zero waste and while reducing global warming, we can help change the climate and increase income from eco enzymes sold. In community service activities, all group members come to the partner to get direction and material on the eco enzyme making process and the benefits obtained. The income obtained by the farmer group or PKK mothers in one eco enzyme harvest is IDR 285,000. Eco enzyme materials such as kitchen waste in the form of unused vegetable scraps and fruit peels.